Effect of temperature on strain-induced hardness of lead-free solder wire using nanoindentation approach - Norliza Ismail,; Maria Abu Bakar,; Saiful Bahari Bakarudin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Hardness properties of SAC305 solder wire under tensile test at varied temperature was investigated. Continuous multicycle (CMC) nanoindentation technique with ten cycle of indentation for each sample was performed to evaluate the hardness behaviour of SAC305 solder wire at different depth of indentation. As a result, all investigated SAC305 solder wire under constant strain rate of tensile test and at different temperature revealed the occurrence of indentation size effect (ISE). At initial cycle of indentation, SAC305 solder wire at room temperature (25 °C) have higher hardness value compared to the others sample which exposed to the varied temperature during tensile test. Besides, higher temperature causes the higher strain or elongation to the SAC305 solder wire. Applied of strain during the tensile test had generated the pre-dislocation activity in the SAC305 solder wire. Therefore, higher hardness values of SAC305 at room temperature is due to the existence of high dislocation density induced by the applied strain. Nevertheless, the existence of heat at 60, 90, 120 and 180 °C during the tensile test prompt the rearrangement of dislocation and reduce the dislocation activities, thus, allowing higher elongation of solder wire.